2020
DOI: 10.2174/1874149502014010094
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Affecting the Performance of Construction Projects in Gaza Strip

Abstract: Background: The construction industry is generally associated with a high level of risk and ambiguity because of the nature of its working contexts. In the Gaza Strip, construction projects are among the riskiest projects, which require the application of the right rules and adherence to the proper management standards. Identification of these risks is the first step in risk management. Aims: This study aims to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“… [ 58 , 59 ] Developing plans to simulate the consequences of project implementation in light of the pandemic through risk simulation programs and measure the risks involved in the implementation. [ 60 , 61 ] Abandonment of talent and expertise by business owners during the pandemic period. [ 62 ] At the project level, changing the cost, risk and implementation management mechanism for daily management and forming an emergency team to avoid sudden emergency risks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 58 , 59 ] Developing plans to simulate the consequences of project implementation in light of the pandemic through risk simulation programs and measure the risks involved in the implementation. [ 60 , 61 ] Abandonment of talent and expertise by business owners during the pandemic period. [ 62 ] At the project level, changing the cost, risk and implementation management mechanism for daily management and forming an emergency team to avoid sudden emergency risks.…”
Section: Literature Reviewmentioning
confidence: 99%
“… [ 62 ] At the project level, changing the cost, risk and implementation management mechanism for daily management and forming an emergency team to avoid sudden emergency risks. [ 61 , 63 , 64 ] Forming small teams and groups in project management to avoid pressure on the general manager of the company or institution. [ 60 , 65 ] Study alternatives for implementation in municipalities, institutions and companies to reduce harm, such as reducing material import operations and reliance on available local materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The construction industry contributes a valuable amount to the economy of any country, however, it is still badly affected by several issues such as cost overrun [ 1 , 2 ], time overrun [ 3 , 4 , 5 ], price fluctuation due to inflation [ 6 , 7 , 8 ], and most importantly due to poor safety performance [ 9 ]. Despite these severe issues, a project gets completed, but is not declared successful because the project failed to achieve the projects’ objectives [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is imperative to control VOs in a construction project [2]. Tayeh et al, 2020, identified the causes of VO as lack of materials and equipment spare parts due to closure, change in design by a consultant, lack of consultant's knowledge of available materials, errors and omission in design, conflicts between contract documents, owner's financial problems, lack of coordination among project parties, using the inadequate specification for local markets by an international consultant, internal politics, and change is a specification by owners [3]. Odenigbo et al, 2020, suggested the causes of VO as client, consultant, contractors, and others.…”
Section: Introductionmentioning
confidence: 99%